2016
DOI: 10.1007/s10534-016-9951-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of antimicrobial activity among new sulfonamide metal complexes for combating rapidly growing mycobacteria

Abstract: Mycobacteriosis is a type of infection caused by rapidly growing mycobacteria (RGM), which can vary from localized illness, such as skin disease, to disseminated disease. Amikacin, cefoxitin, ciprofloxacin, clarithromycin, doxycycline, imipenem and sulfamethoxazole are antimicrobial drugs chosen to treat such illnesses; however, not all patients obtain the cure. The reason why the treatment does not work for those patients is related to the fact that some clinical strains present resistance to the existing ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The cadmium complexes were less toxic, with the most active species (X = SCN) showing a MIC of 25 µg/mL against P. aeruginosa. In 2016, Agertt et al evaluated sulfonamide metal complexes of Au, Ag, Cd, Cu and Hg for their antimycobacterial activities against M. abscessus, M. fortuitum and M. massiliense [191]. Cadmium and mercury complexes showed MICs of 4.9 µg/mL against M. fortuitum and M. massiliense and of 19.5 and 9.8 µg/mL, respectively, against M. abscessus.…”
Section: Cadmium and Mercury Complexesmentioning
confidence: 99%
“…The cadmium complexes were less toxic, with the most active species (X = SCN) showing a MIC of 25 µg/mL against P. aeruginosa. In 2016, Agertt et al evaluated sulfonamide metal complexes of Au, Ag, Cd, Cu and Hg for their antimycobacterial activities against M. abscessus, M. fortuitum and M. massiliense [191]. Cadmium and mercury complexes showed MICs of 4.9 µg/mL against M. fortuitum and M. massiliense and of 19.5 and 9.8 µg/mL, respectively, against M. abscessus.…”
Section: Cadmium and Mercury Complexesmentioning
confidence: 99%
“…In contrast, the ternary Cu(II) complexes associating sulfathiazole and a series of cephalosporins (cefazolin, cefalotin, cefotaxime and ceftriaxone) reported by Anacona et al did not prove to be characterized by the same synergetic effect; their antibacterial activity was comparable to that of the free cephalosporin [3]. The antibacterial activity of ternary complexes of Ag(I) and Au(I) with sulfonamides and phosphine derivatives, respectively (Table I), was reported with interesting results [1,2,[33][34][35]. The study of the Au(I) monomer complex and Ag(I) polymeric complex with sulfamethoxazole reported by Marques et al concluded that these complexes exhibited significant antibacterial properties against E. coli, S. aureus and P. aeruginosa.…”
Section: Sulfonamide-containing Metal Complexes With Antibacterial Propertiesmentioning
confidence: 95%
“…Compound 37 and 38 ( Figure 6) in a different study were also assessed for their activity and synergistic activity with trimethoprim in different species of Mycobacterium (M. abscessus, M. forticum and M. massiliense) responsible for nosocomial infections that are typically not transmitted human to human but rather from the environment. [68] Significant improvement in activity was observed upon conjugation to a {Au(PPh 3 )} + center and synergy between 37 or 38 and trimethoprim was observed in most cases with these Mycobacterium species. In our laboratory, complex 52 ( Figure 8) with known TB drug pyrazinamide as an N donor ligand was first screened for its activity towards M. smegmatis (MIC = 60 μM) and had a higher activity than the control drug isoniazid.…”
Section: Antiparasitic Activitymentioning
confidence: 96%
“…The synergy between trimethoprim and 51 was also observed with M. tuberculosis providing promising results for future studies. Compound 37 and 38 (Figure 6) in a different study were also assessed for their activity and synergistic activity with trimethoprim in different species of Mycobacterium ( M. abscessus, M. forticum and M. massiliense) responsible for nosocomial infections that are typically not transmitted human to human but rather from the environment [68] . Significant improvement in activity was observed upon conjugation to a {Au(PPh 3 )} + center and synergy between 37 or 38 and trimethoprim was observed in most cases with these Mycobacterium species.…”
Section: Antimycobacterial Activitymentioning
confidence: 99%